Health Benefits and Participation Barriers of Different Level Horseback Riders Age-Wise - Sáez, Iker; León-Guereño, Patxi; Malchrowicz-Mośko, Ewa; Balerdi, Eneko; Río, Xabier; Lavín, Beñat; Solabarrieta, Josu (Frontiers in Psychology, 2022)
Although horseback riding is not specifically mentioned in the recommendations for different age groups regarding the level of physical activity necessary for good health, its practice continues to grow in popularity throughout the world. Despite being a minority discipline, it has some characteristics that make it an opportunity for its participants to be active people, so it is important to understand what are the perceived health benefits and barriers to participation. The aim of the study is to describe and analyze the perceived health benefits and barriers in horseback riding among riders categorized by level and age, in order to promote physical activity through these benefits and to overcome the barriers. An online version of the EBBS (Exercise Benefits/Barriers Scale) was used to analyze benefits and barriers. The sample consisted of 2651 participants (95.9% men and 4.1% women) in an equestrian event, distributed in four age groups (79.4% up to 25 years, 11.5% between 26 and 35, 7.9% between 36 and 50, 1.2 older than 50 years). Perceived benefits and participation barriers to horseback riding were analyzed. The factor analysis identified and confirmed 5 benefit factors and 4 barrier factors. Benefit factors were significantly correlated among them but barriers were less interrelated. Higher ages were associated to larger benefits and less barrier effects. Benefit and barrier differences were larger between amateur and professional riders, compared to gender differences.